2020
DOI: 10.1016/j.cmi.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infection caused by KPC-producing Klebsiella pneumoniae resistant to ceftazidime/avibactam: epidemiology and genomic characterization

Abstract: Aim of this study was to evaluate the incidence of ceftazidime/avibactam resistance among KPCproducing Klebsiella pneumoniae (KPC-Kp) strnins isolated from patients with bloodstream infection. MethodsWe collected 120 carbapenemase producing Enterobacteriaceae (CPE) strnins from unique patients hospitalized in two Italian hospitals between Januaiy 2018 to Febmaiy 2019. Strains were phenotypically characterized for the type of carbapenemase production and susceptibility to ceftazidime/avibactam. Ceftazidime/avib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 11 publications
6
42
0
Order By: Relevance
“…At the same time, our results showed that no speci c mutations were observed in KPC-Kp isolates resistant both to meropenem/vaborbactam and ceftazidime/avibactam in comparison to strains resistant to meropenem/vaborbactam alone. These results are in accordance with previous ndings that showed as cross-resistance to meropenem/vaborbactam and ceftazidime/avibactam was due to loss-of-function mutations in the OmpK35 and OmpK36 porins which are also associated to elevated MICs for ß-lactams [4,5].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…At the same time, our results showed that no speci c mutations were observed in KPC-Kp isolates resistant both to meropenem/vaborbactam and ceftazidime/avibactam in comparison to strains resistant to meropenem/vaborbactam alone. These results are in accordance with previous ndings that showed as cross-resistance to meropenem/vaborbactam and ceftazidime/avibactam was due to loss-of-function mutations in the OmpK35 and OmpK36 porins which are also associated to elevated MICs for ß-lactams [4,5].…”
Section: Discussionsupporting
confidence: 93%
“…Bacteria was identi ed by MALDI-TOF (Bruker Daltonics, Germay) and antimicrobial susceptibility testing was performed by MicroScan Walkaway system and con rmed by MIC test strip (Lio lchem, Italy). The MIC value for colistin was determined by reference broth microdilution method [4]. MIC results were interpreted according to EUCAST clinical breakpoints v11.0 (http://www.eucast.org/clinical_breakpoints/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Since there is no history of previous antimicrobial exposure to CAZ/AVI treatment or specific mutations were observed in the bla KPC-2 gene, hyperexpression of the bla KPC-2 gene associated with alteration in the outer membrane or other unknown mechanisms might account for this low level of CAZ/AVI resistance. 28 The transconjugants exhibited reduced resistance levels to carbapenems compared with clinical isolates. The copy number of genes and selective expression of promoters in strains of different species or genera, 29 restoration of deficient Omp proteins, and antibiotic selection pressure could influence the MIC level of the transconjugants.…”
Section: Discussionmentioning
confidence: 98%
“…Intriguingly, in addition to the high level of carbapenem resistance with a meropenem MIC of 1,024 mg/L, the strain KP3034 exhibited a higher MIC level for CAZ/AVI (16/4 mg/L) than the other strains detected. As no history of previous antimicrobial exposure to CAZ/AVI treatment or speci c mutations were observed in the bla KPC−2 gene, hyper-expression of the bla KPC−2 gene associated with porin de ciency in the outer membrane, or other unknown mechanisms might account for this low level of CAZ/AVI resistance [25] .…”
Section: Discussionmentioning
confidence: 98%